Manajemen Peserta Didik dalam Meningkatkan Efektivitas Perkembangan Anak Usia Dini - Neti Riana; Nevi Laila Khasanah; Mansur Romadon Putra (STAI Bumi Silampari, 2025)
Early Childhood Education (PAUD) is a critical phase for the formation of children's character and intelligence, but many institutions still face obstacles in administrative management and documentation of student development that have not been integrated. This study aims to conduct a comprehensive analysis of student management to improve the effectiveness of early childhood development which includes physical, cognitive, social, and emotional aspects. The research method used is qualitative with a library research approach, where data is collected through searching various scientific literature and official documents, then analyzed using content analysis techniques. The results of the study show that effective student management must be carried out through systematic stages, starting from needs analysis, orientation periods, to objective evaluation of learning outcomes. Collective commitment, educator professionalism, and strong synergy between schools and parents are the main pillars in creating a conducive learning ecosystem. In addition, the management of special services and the use of digital technology in administration are indispensable to ensure that each child's unique potential can be detected and developed optimally. The implementation of this integrated management has been proven to be able to improve the quality of educational services and support children's growth holistically.